1998
DOI: 10.1016/s0168-6496(98)00009-9
|View full text |Cite
|
Sign up to set email alerts
|

Slow-growing and oligotrophic soil bacteria phylogenetically close to Bradyrhizobium japonicum

Abstract: Eleven isolates of slow-growing oligotrophic bacteria from grassland soil were found to be closely related by partial 16S rRNA sequence similarity and many common taxonomic traits. Analysis of full 16S rRNA gene sequences of four representative isolates and Agromonas oligotrophica S58 indicated that they were more closely related to Bradyrhizobium japonicum, a symbiotic nitrogen-fixing bacterium, (similarity values: 98.1^98.8%) than other strains such as Bradyrhizobium elkanii, Nitrobacter spp., Rhodopseudomon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 10 publications
1
32
0
3
Order By: Relevance
“…In support of this, Mitsui et al (25) and Klappenbach et al (21) found slow-growing oligotrophic ␣-Proteobacteria to be more dominant in soil. In the former study, many of these isolates were nonsymbiotic members of the Rhizobiaceae and Bradyrhizobiaceae (25,26), families that have genomes Ͼ6-8 Mb. Generation times in soil are thought to be low, with mean generations measured at three per year (27).…”
Section: Resultsmentioning
confidence: 99%
“…In support of this, Mitsui et al (25) and Klappenbach et al (21) found slow-growing oligotrophic ␣-Proteobacteria to be more dominant in soil. In the former study, many of these isolates were nonsymbiotic members of the Rhizobiaceae and Bradyrhizobiaceae (25,26), families that have genomes Ͼ6-8 Mb. Generation times in soil are thought to be low, with mean generations measured at three per year (27).…”
Section: Resultsmentioning
confidence: 99%
“…Symbiosis loci required for host nodulation and nitrogen fixation are clustered onto large plasmids or genomic islands [15][16][17][18][19], that can be transferred among lineages, presumably via conjugation [20][21][22]. Non-nodulating rhizobia are also common [23,24], and these strains often lack some or all of the characterized symbiosis loci [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Members of Bradyrhizobiaceae include a number of nonsymbiotic bacteria with diverse biochemical functions such as photosynthesis (Molouba et al, 1999;Larimer et al, 2004;Giraud et al, 2007), oligotrophy (Saito et al, 1998;King, 2007), 2,4-dichlorophenoxyacetic acid degradation (Kamagata et al, 1997) and nitrification (Starkenburg et al, 2006).…”
Section: Introductionmentioning
confidence: 99%